Mechanochemical Preparation of Biomass-Derived Porous Carbons - Jerzy Choma; Barbara Szczęśniak; Mietek Jaroniec (Molecules)
Conventional methods for the synthesis of porous carbons are typically time- and energy-consuming and often contribute to the excessive accumulation of waste solvents. An alternative approach is to employ environmentally friendly procedures, such as mechanochemical synthesis, which holds great potential for large-scale production of advanced carbon-based materials in coming years. This review covers mechanochemical syntheses of highly porous carbons, with a particular focus on new adsorbents and catalysts that can be obtained from biomass. Mechanochemically assisted methods are well suited for producing highly porous carbons (e.g., ordered mesoporous carbons, hierarchical porous carbons, porous carbon fibers, and carbon–metal composites) from tannins, lignin, cellulose, coconut shells, nutshells, bamboo waste, dried flowers, and many other low-cost biomass wastes. Most mechanochemically prepared porous carbons are proposed for applications related to adsorption, catalysis, and energy storage. This review aims to offer researchers insights into the potential utilization of biowastes, facilitating the development of cost-effective strategies for the production of porous carbons that meet industrial demands.